2020
DOI: 10.1080/07352166.2020.1768103
|View full text |Cite
|
Sign up to set email alerts
|

The intra-urban residential and workplace locations of small business owners

Abstract: The notion that buzz, creativity, diversity, openness and a sense of bohemia in cities are important to attract creative workers and entrepreneurs has grown in prominence both in academic literatures and in city economic development strategies. However, there is a disjuncture in the literature and dearth of evidence as to whether entrepreneurs seek bohemian (open, diverse) places in which to live or to locate their business. This study explores the kinds of neighborhood small business owners, in particular ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
(103 reference statements)
0
3
0
1
Order By: Relevance
“…As a consequence, work has increasingly been organised outside employer–employee systems, and people hold multiple jobs, or work freelance alongside a job. This has resulted in substantial changes to the spaces and places of work and business activities (Koroma et al, 2014; Merkel, 2019; Reuschke and Houston, 2020; Stam and van de Vrande, 2017). Previous research has sought to measure nonstandard employment in particular cities and has revealed that the so-called ‘contingent workforce’ (those working as self-employed, part-time and/or from home) has increased in size.…”
Section: Beyond the Traditional Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, work has increasingly been organised outside employer–employee systems, and people hold multiple jobs, or work freelance alongside a job. This has resulted in substantial changes to the spaces and places of work and business activities (Koroma et al, 2014; Merkel, 2019; Reuschke and Houston, 2020; Stam and van de Vrande, 2017). Previous research has sought to measure nonstandard employment in particular cities and has revealed that the so-called ‘contingent workforce’ (those working as self-employed, part-time and/or from home) has increased in size.…”
Section: Beyond the Traditional Workplacementioning
confidence: 99%
“…These factors, amongst others, have contributed to the practice of working from home and the emergence of collaborative working spaces such as coworking spaces. This means that we need to think of residential neighbourhoods not purely as places to live but also as places of work and the location of micro-business activities (Ekinsmyth, 2013; Folmer, 2014; Kane and Clark, 2019; Reuschke and Houston, 2020). It is likely that the emergence of new workspaces changes the nature of their surrounding areas, for example through the attraction of more day-time population or a shift in residential composition.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, more effort needs to be made to improve its effectiveness. Taken together, micro-business owners need to take more initiatives to seize all the opportunities around them (Reuschke & Houston, 2020;Owoseni et al, 2020;Yusof & Tahir, 2021).) Moreover, they should be more willing and daring to explore new areas of business that have not been ventured into (Hantman & Gimmon, 2014;Jain & Khandelwal, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…赖创新促进技术进步的新局面 [3] 。如何在新一轮的 世界创意产业分工中抓住机会并促进城市创新发展 成为该时代背景下需要思考和关注的热点问题 [4] 质生活的新的城市发展理论 [2] 。 城市舒适性理论有三大代表性思想。其一, Florida [14] 提出 "创意阶层" , 认为创意阶层对区域经 济活力至关重要。创意阶层促进当地 "创意" 的产 生, 通过高水平的创新以及技术密集型产业扩张的 形式对区域经济增长产生积极影响。那么, 为什么 创意阶层选择集聚在某个区域范围内呢?Florida [14] 认为是城市中的便利设施、 社会氛围的包容性和城 市的多样性促使创意阶层集聚。其二, Glaeser 等 [15] 提出消费城市(consumer city), 认为城市发展在一定 程度上取决于城市的各项设施以及个人偏好的复 杂权衡, 包括考虑城市的气候、 生活质量、 住房成 本、 工作薪酬等。其三, Clark 等 [5] 、 Bartlett 等 [16] [17] 率先使用的基于不动产价值和工资建立的 Hedonic 价格模型应用较为广泛, 大部分学者普遍接受使用 房租和工资水平表征城市舒适程度, 即当一个城市 具有极高的舒适性时, 人们就愿意支付相对高的房 租并忍受相对低的收入来获取舒适性。继 Rosen 之 后, Hedonic 模型法在城市舒适性的理论和实证研 究中得到广泛应用 [18][19] 。问卷调查和访谈的方法常 应用于研究城市舒适性对个人或企业选址决策的 影响, Rik 等 [20] 利用问卷调研荷兰时装设计企业家 在城市内部的选址决策, 结果显示, 设计师关注包 容的社会氛围、 丰富的文化设施、 激发灵感的场所 以及时尚城市的名声, 于是阿姆斯特丹成为最佳选 址。Reuschke 等 [21] 探究爱丁堡的创业型小企业家 选择办公地点以及家庭住址是否会被城市舒适性 要素中的波西米亚风格(开放、 多样性)所吸引, 并与 表 1 城市舒适性概念与内涵的探讨 Tab.1 The concept and connotation of urban amenity 学者 Ullman [1] Bartik 等 [6] Power [7] Gottlieb [8] Luger [9] Glaeser [10] Clark 等 [5] Scott [11] Mulligan 等 [12] Zheng [13] 的评价指标体系。Boyer 等 [22] 首次建立起较为全面 的城市舒适性评价指标体系, 将城市舒适性分为生 活成本、 犯罪、 医疗、 工作、 交通、 教育、 艺术、 休闲和 气候等 9 个指标。之后, 城市学家通过多个实证案 例得出社会氛围舒适性, 即多样性和包容性有助于 城市的增长和发展的结论。2002 年, Florida [23] 提出 波西米亚指数(Bohemian Index), 认为波西米亚人在 某一地区的存在和集中创造了一种开放、 包容以及 多样性的环境氛围, 吸引着其他类型的人才或高人 力资本的个人。人力资本的累积又吸引着以技术 为基础的产业或促进创新产出, 进而促进城市可持 续发展。同年, Florida [24] 还提出多样性指数, 使用研 究区域内总人口中同性恋家庭所占的比重来表征 城市多样性和包容程度。也有学者在 POV Magazine 中提出使用 "coolness factor" , 该指标包括年轻 人的占比、 城市夜生活(例如酒吧的数量等)状况以 及拥有文化设施的数量等 [23] 。 1.4 城市舒适性影响的实证研究 利用 CiteSpace 对 web of science (WoS)的核心 数据集进行检索, 以 urban amenity 和 amenity 为主 题词进行搜索, 并选择 urban studies、 geography 和 regional urban planning 三个领域, 时间尺度获取为…”
unclassified